Recent Advances in Nanostructured Transition Metal Carbide- and Nitride-Based Cathode Electrocatalysts for Li–O2 Batteries (LOBs): A Brief Review - K. Karuppasamy; K. Prasanna; Vasanth Rajendiran Jothi; Dhanasekaran Vikraman; Sajjad Hussain; Jung-Hoon Hwang; Hyun-Seok Kim (Nanomaterials, 2020)
A large volume of research on lithium–oxygen (Li–O2) batteries (LOBs) has been conducted in the recent decades, inspired by their high energy density and power density. However, these future generation energy-storage devices are still subject to technical limitations, including a squat round-trip efficiency and a deprived rate-capability, due to the slow-moving electrochemical kinetics of both the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) over the surface of the cathode catalyst. Because the electrochemistry of LOBs is rather complex, only a limited range of cathode catalysts has been employed in the past. To understand the catalytic mechanisms involved and improve overall cell performance, the development of new cathode electrocatalysts with enhanced round-trip efficiency is extremely important. In this context, transition metal carbides and nitrides (TMCs and TMNs, respectively) have been explored as potential catalysts to overcome the slow kinetics of electrochemical reactions. To provide an accessible and up-to-date summary for the research community, the present paper reviews the recent advancements of TMCs and TMNs and its applications as active electrocatalysts for LOBs. In particular, significant studies on the rational design of catalysts and the properties of TMC/TMN in LOBs are discussed, and the prospects and challenges facing the continued development of TMC/TMN electrocatalysts and strategies for attaining higher OER/ORR activity in LOBs are presented.